Anatomical variations of the stylopharyngeus and superior constrictors in relation to their function - Choi, Da-Yae (Anat Cell Biol, 2020)
The aims of this study were to clarify the topography and variations stylopharyngeus (STP) and superior constrictor (SC) muscles, and to examine what role they play in the pharyngeal movement. Forty-four specimens (22 right and 22 left sides) from embalmed Korean adult cadavers (13 males, 9 females; age range, 46–89 years; mean age, 69.2 years) were used in this study. The accessory bundle of STP and petropharyngeus was found in 18.2% (8/44) and 25.0% (11/44) of cases, respectively. A variation of the STP, in which it ran transversely and merged with the SC muscle, was found in 2.3% (1/44) of cases while a variation of the SC muscle, in which it ran longitudinally and merged with the contralateral constrictors, was found in 11.4% (5/44). The variant muscle bundles play their own role in pharyngeal movement according to their morphology. These results provide information that will help a comprehensive understanding of the effects of pharyngeal muscles on movement.